Laparoscopic examination of reproductive tract in buffaloes - SINGH, BHOOPENDRA; RAWAL, C V S (The Indian Journal of Animal Reproduction, 2023)
Laparoscopy in three infertile buffaloes revealed that fasting helps in better laparoscopic visualization of organs creating more space inside the peritoneal ci1vity and sufficient pneumo-peritoneum due to air insuffilltions. Laparoscopy was performed more easily through right paralumbar fossa approach than left paralumbar fossa approach as it was time consuming, disadvantageous for accidental puncturing of rumen and also provided less space to manipulate the laparoscope. Uterine horns were seen as reddish coloured tapering tubes, <:!early distinct from other organs. Large follicle was seen as translucent area on the ovarian surface.